Micro-Characterization of Recycled Concrete Aggregate (Journal of Engineering Science, 2024)
Recycled concrete aggregate (RCA) is generated by crushing and processing concrete waste from demolition and construction activities, thereby reducing the environmental burden associated with disposing of concrete debris. The use of RCA in concrete production helps to alleviate the depletion of natural resources, as it serves as a substitute for traditional coarse and fine aggregates. This study identifies the microstructural aspects of RCA concrete, employing advanced techniques like scanning electron microscope (SEM) imaging with energydispersive spectroscopy (EDS) to analyze the microstructure and chemical composition of recycled concrete. The detailed microstructural analysis is anticipated to elucidate how the RCA content influences the interfacial transition zone, bond strength, and overall concrete performance. RCA exhibits a unique microstructure due to the presence of attached old mortar, which can influence the overall performance of RCA concrete. This study also explores the utilization of 100% RCA in preparing recycled concrete, comparing it with old and ordinary new concrete. The focus is on microstructural properties, hydration products, and the Interfacial Transition Zone (ITZ) between cement paste and aggregates. Samples were collected from a 47-year-old building, separating aggregates into different grades. Recycled coarse aggregates and recycled fine aggregates were obtained, and natural aggregates were collected. Concrete mixes for recycled and natural concrete were designed for a test strength of C30. Concrete cylinders were tested for compressive strength at 7, 28, and 90 days. Old concrete exhibited a dense microstructure with well-formed C-S-H gels, contributing to its superior strength. Recycled concrete, however, showed a wider and less dense ITZ, resulting in a more porous microstructure. EDS spectra confirmed C-S-H gel as the primary hydration product in all mixes, with the Ca/Si ratio varying, indicating complexity in hydrated product formation. The research highlights differences in microstructural and chemical characteristics among old concrete, ordinary new concrete, and recycled concrete. The wider ITZ and more porous microstructure in recycled concrete contribute to reduced strength. These findings provide insights into sustainable construction practices, promoting the use of recycled materials and addressing environmental challenges in the construction industry. As the construction industry continues to embrace sustainability, further research into the properties, performance, and best practices for incorporating RCA into concrete will play a pivotal role in advancing eco-friendly construction methodologies.Journal of Engineering Science 14(2), 2023, 145-155